2020
DOI: 10.1142/s0218202520400072
|View full text |Cite
|
Sign up to set email alerts
|

Global generalized solutions to a forager–exploiter model with superlinear degradation and their eventual regularity properties

Abstract: In this paper, we consider a cascaded taxis model for two proliferating and degrading species which thrive on the same nutrient but orient their movement according to different schemes. In particular, we assume the first group, the foragers, to orient their movement directly along an increasing gradient of the food density, while the second group, the exploiters, instead track higher densities of the forager group. Specifically, we will investigate an initial boundary-value problem for a prototypical … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…where Ω ⊂ R 2 is a bounded open domain with smooth boundary ∂Ω, and the parameters µ, µ 1 , µ 2 , λ, m and l are some positive constants. Moreover, we suppose that 2 ≤ m < 3 and l ≥ 3,…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…where Ω ⊂ R 2 is a bounded open domain with smooth boundary ∂Ω, and the parameters µ, µ 1 , µ 2 , λ, m and l are some positive constants. Moreover, we suppose that 2 ≤ m < 3 and l ≥ 3,…”
mentioning
confidence: 99%
“…For instance, the shearwater flocks and kittiwake foragers, the death of individuals at high population densities should not be neglected. Thus, as n = 2, Black in [2] discussed the existence of the global generalized solutions to the forager-exploiter model with logistic sources f (u) and g(v), and supposed that…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike the simple structure in the minimal Keller-Segel system or the prey-taxis model, the different taxis strategies in the system (1.3) produce more mathematical challenges and make the analysis work more complicate and difficult. Motivated by the arguments in previous studies [4,32,37,40,41], we proved that system (1.3) admits at least a generalized solution for any choice of m > 1 + √ 2 and l > m+1 m−1 , where the small initial value conditions (1.6) and (1.7) in [37] is not necessary anymore. Now, we state our main result.…”
mentioning
confidence: 81%
“…When n ≥ 1 and η 1 = η 2 = 0, by taking into account the volume-filling effect and 0 ≤ u 0 , v 0 ≤ 1, the global existence of the classical solutions was built in [18]. When n = 2 and η 1 = η 2 > 0, Black [4] showed that (1.3) has at least one global generalized solution if m > √ 2 + 1 and min{m, l} > (m + 1)/(m − 1), and proved that the generalized solution actually becomes a classical one after some waiting time under conditions: m, l > √ 2 + 1, r ≥ 0 satisfies (1.4) and r ∈ L 1 ((0, ∞); L ∞ (Ω)). In the same case, Wang and Wang [32]…”
mentioning
confidence: 99%